Hot water immersion disinfests enset (Ensete ventricosum) suckers from the enset root mealybug Cataenococcus ensete Williams and Matile-Ferrero - Lemawork, S.; Azerefegne, F.; Alemu, T.; Addis, T.; Blomme, Guy (Academic Journals, 2018)
The enset root mealybug, Cataenococcus ensete Williams and Matile-Ferrero (Homoptera: Pseudococcidae) is a pest of national significance attacking enset in south and south-western Ethiopia. Adults and nymphs of several overlapping generations feed on the crops’ underground corms and roots, making them hard to reach and thus control. The main means of pest spread is through infested planting material. The objective of this study was to evaluate the effect of a hot water treatment of enset suckers against enset root mealybugs. Small, medium and large-sized infested enset suckers were each exposed to water temperatures of 21, 55, 75 and 95°C for periods of 10, 30, 60 and 300 s. Complete mealybug mortality was obtained for 60 s at 55°C and at 10 and 30 s exposure times at 75 and 95°C without affecting the performance of enset suckers of all size groups. Considering the ease of using boiling water for small-scale enset farmers, immersing suckers for at least 10 and up to 30 s at 95°C is advocated in order to eliminate all enset root mealybugs from enset suckers. The immersion of enset suckers in boiling water for 10 to 30 s can be easily demonstrated, with a much higher envisaged adoption rate by farmers.